The importance of market studies in public procurement (2019)
Public procurement in Colombia has as its main objective to fulfill the essential purposes of the state. To execute these purposes, the government must acquire goods and services in an economic manner, giving as an effect the best possible quality for the price paid to satisfy the needs of the entity. Given the above, entities should know the market of the goods and services they intend to acquire in order to be as transparent and efficient as possible, analyzing the prices and conditions to achieve the best possible decision. This writing seeks to know or verify what is the importance of market studies in government procurement, likewise, make a review of good practices when making a sectoral economic study of public procurement in Colombia, which allows greater competitiveness among companies and achieve greater economic growth.